Feasibility analysis on the potential of photovoltaic applications in Peninsular Malaysia / Ali Wadi Abbas Al-Fatlawi - Ali Wadi Abbas, Al-Fatlawi (2015)
This study was conducted to enhance the utilization of renewable energy resources to contribute towards national electricity supply sustainability and sustainable socio-economic development. Four methodologies were developed starting with solar radiation modeling using artificial neural networks (ANNs), followed by modeling and investigating the feasibility of grid-connected solar PV applications under the Feed-in-Tariff (FIT) program. After that, a sensitivity analysis was developed based on economic indicators. Next, a solar PV power hybrid standalone street light application was modeled for remote areas where electricity extension can be made cost-effective. Lastly, people's acceptance, and obstacles to using solar energy applications were investigated. The outcomes of the resource analyses show that the ANN solar maps are sufficiently accurate to be utilized with solar radiation applications in Peninsular Malaysia, whereby from all 12 designed models, the mean absolute percentage error (MAPE) was less than 6.07%. The model with a MAPE value of 4.04% and correlation (R) of 0.965 attained a fairly steady reading, which can be safely inferred as a high reliability level in terms of weather data prediction. Solar radiation mapping indicates the annual radiation in Peninsular Malaysia is between 3.88 and 5.13 kWh/m2/day. However, the northeast region has the highest potential for solar energy throughout the year. In this context, the renewable energy outputs from the grid-connected solar PV in pilot locations varied between a maximum of 1.312 MWh/kWp in Lubok Merbau and a minimum of 1.010 MWh/kWp in Cameron Highlands, with capacity factors of 15% and 11.5% respectively. The cost of electricity ranges from $0.36/kWh for the most favorable locations to $0.28/kWh for less favorable locations, while the mean cost in the entire peninsular region is about $0.31/kWh. Government incentives are expected to reduce the payback period by approximately 73%, with the current payback periods ranging from a minimum of 7.4 years in Beyan Lepas to a maximum of 9.6 years in Cameron Highlands, while the mean payback period in Peninsular Malaysia is expected to be 8 years. According to a street light application analysis, using renewable energy-based solar radiation for street lighting is not recommended in Malaysia mostly due to the frequent occurrence of continuously heavy cloud cover and rainy days. Such conditions require a proportionate increase in PV size as well as number of batteries in order to adequately harvest the required energy in a shorter time span, hence causing an overall increase in the cost of providing street light poles. Based on the social acceptance of solar energy technology, the survey shows significant potential to implement solar PV applications in Malaysia. Nonetheless, there has also been considerable failure to provide promotional informative features of solar PV applications, where people are still not even familiar with the term Feed-in-Tariff. However, around 36% are potentially ready to begin PV projects but require loans to reduce the starting capital costs, even if the loans stipulate sharing the FIT benefits with banks in advance.